The Efforts to Control and Prevent Cervical Cancer Through Early Detection Using The VIA Test in Health Office of East Java Province - Zulham, Riza Muhammad; Wahyuni, Chatarina Umbul; Isfandiari, Muhammad Atoillah; Huda, Hasan (Health Notions, 2018)
-